2000
DOI: 10.1139/b00-023
|View full text |Cite
|
Sign up to set email alerts
|

Epiphytic bryophytes on European aspenPopulus tremulain old-growth forests in northeastern Finland and in adjacent sites in Russia

Abstract: We studied the occurrence and cover of epiphytic bryophytes and one lichen species (Lobaria pulmonaria (L.) Hoffm.) growing on Populus tremula L. trunks. Our aim was to explore the spatial scales where epiphyte species respond to their environment. At the landscape scale, fragmented Finnish old-growth forests close to the Russian border and farther west in a heavily fragmented landscape were compared with Russian sites with more continuous old-growth forest landscapes to assess the effect of landscape structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 21 publications
2
16
1
Order By: Relevance
“…Contrary to these results, several authors have reported that tree DBH does not strongly impact epiphytic bryophytes [32][33]. The possible explanations for the differences between this study and previous studies are as follow.…”
Section: The Significance Of Shrine Forestscontrasting
confidence: 98%
See 1 more Smart Citation
“…Contrary to these results, several authors have reported that tree DBH does not strongly impact epiphytic bryophytes [32][33]. The possible explanations for the differences between this study and previous studies are as follow.…”
Section: The Significance Of Shrine Forestscontrasting
confidence: 98%
“…Epiphytic bryophytes are affected by environmental factors such as tree density [15,33], past landscape structure [18,34], bark type [39], silvicultural disturbance [40], air pollution [41], etc. By examining the influence of these factors on bryophytes in future studies, we can propose more effective methods for the conservation of these species.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, lichen epiphytes are useful indicators of forest health because they are sensitive to forest management practices and serve as indicators of air quality (Lesica et al, 1991;Richardson, 1992;McCune, 2000). According to literature, the most important factors influencing epiphytic bryophyte and lichen distribution are forest stand age (Fritz et al, 2008;Mežaka et al, 2010), host tree (Lõhmus et al, 2007;Mežaka et al, 2008;Strazdina, 2010), tree age (Barkman, 1958;Hedenås & Eriksson, 2000;Ojala et al, 2000) and microclimate (John & Dale, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…High tree density and host tree DBH have been suggested to be beneficial for bryophyte diversity, as they provide better microclimates, e.g., humid conditions (Hazell et al, 1998;Ojala et al, 2000;Thomas et al, 2001). Further, the species richness and bryophyte cover may be positively correlated with high host tree DBH because DBH is correlated with bark features (e.g., bark thickness and bark roughness) (Boudreault et al, 2008;Ojala et al,2000).…”
Section: Resultsmentioning
confidence: 99%
“…Further, the species richness and bryophyte cover may be positively correlated with high host tree DBH because DBH is correlated with bark features (e.g., bark thickness and bark roughness) (Boudreault et al, 2008;Ojala et al,2000).…”
Section: Resultsmentioning
confidence: 99%